INHALANT GLUCOCORTICOID APPLICATION EXPERIENCE AMONG INFANTS WITH BRONCHOPULMONARY DYSPLASIA IN THE FIRST HALF YEAR OF LIFE - I.V. Davydova; G.V. Yatsyk; O.F. Lukina; O.V. Tresorukova (Union of pediatricians of Russia, 2008)
The article describes the modern views on the application of the inhalant glucocorticoids (budesonide suspension) among infants, who underwent artificial pulmonary ventilation at the neonatal stage and who had bronchopulmonary dysplasia formed. The authors performed the clinical and functional evaluation of their state owing to the bronchophonography along with the follow up observation until 6 month of life.Key words: artificial pulmonary ventilation, bronchopulmonary dysplasia, extremely low body weight, bronchophonography, acoustic work of breathing.